2021
DOI: 10.1002/onco.13789
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Very Low-Risk Subgroups of Patients with Primary Mediastinal Large B-Cell Lymphoma Treated with R-CHOP

Abstract: Background. R-CHOP can cure approximately 75% of patients with primary mediastinal large B-cell lymphoma (PMLBCL), but prognostic factors have not been sufficiently evaluated yet. Rda-EPOCH is potentially more effective but also more toxic than R-CHOP. Reliable prognostic classification is needed to guide treatment decisions.Materials and Methods. We analyzed the impact of clinical prognostic factors on the outcome of 332 PMLBCL patients ≤65 years treated with R-CHOP AE radiotherapy in a multicenter setting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 65 publications
0
33
1
Order By: Relevance
“…Dunleavy et al then showed the world remarkable results of a phase II trial with 67 patients submitted to a non-RT-based DA-EPOCH-R, giving this regimen a high scientific acceptance [ 13 ]. However, some later real-life evidences may suggest that, in some specific circumstances, DA-EPOCH-R might not be that better than R-CHOP, and also that the mediastinal RT might still have its role in the management of PMBCL [ 11 , 25 28 ]. Despite all its statistical limitations and bias, our findings find a path with those studies, summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Dunleavy et al then showed the world remarkable results of a phase II trial with 67 patients submitted to a non-RT-based DA-EPOCH-R, giving this regimen a high scientific acceptance [ 13 ]. However, some later real-life evidences may suggest that, in some specific circumstances, DA-EPOCH-R might not be that better than R-CHOP, and also that the mediastinal RT might still have its role in the management of PMBCL [ 11 , 25 28 ]. Despite all its statistical limitations and bias, our findings find a path with those studies, summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of t-MDS/AML after R-DA-EPOCH should be accurately quantified and correlated to the reached dose level, especially in the young population of patients with PMLBCL. The accurate prediction of prognosis is required in order to tailor treatment to the individualized risk of failure [27][28][29] and potentially restrict more toxic chemotherapy to higher-risk patients. Meanwhile, PET/CT might facilitate the omission of radiotherapy in lower-risk patients [4][5][6]29] in strictly negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above data, the clinical stage was IVB, the International Prognostic Index (IPI) was 2 and the age-adjusted IPI was also 2 falling into the low/intermediate and high/intermediate risk group respectively. However, this case is considered as “high-risk” based on extranodal involvement and highly elevated LDH (>2xULN) or bulky disease according to the scoring system, which was recently published by our group ( Vassilakopoulos et al, 2021 ).
Fig.
…”
Section: Case Presentationmentioning
confidence: 99%
“…PMLBCL is an uncommon thymic neoplasm of B-cell origin accounting for approximately 2.5% of non-Hodgkin lymphomas (NHL) ( Swerdlow et al, 2017 ). Unlike most cases of diffuse large B-cell lymphoma (DLBCL), PMLBCL typically affects young and middle-aged adults with a female predominance ( Vassilakopoulos et al, 2012 , Savage et al, 2006 , Vassilakopoulos et al, 2021 ). The majority of patients present with bulky mediastinal lymphadenopathy often causing dyspnea, dry cough and occasionally the superior vena cava syndrome.…”
Section: Introductionmentioning
confidence: 99%